Legal Protection for the Victims of Religious Hate Speech on the Internet - Agus Raharjo; Yusuf Saefudin; Sonny Zulhuda (Kosmik Hukum, 2023)
Over recent decades, the boom in information and communication technologies (ICTs) has brought completely new ways of establishing and maintaining relationships. Nevertheless, in very different ways, people are vulnerable to multiple forms of violence that threaten their physical and psychological integrity. Various media and new technologies are explored, but particularly the Internet and mobile phones and the convergence between the two are discussed. The religious hate speech was easily found on the internet. The victims on certain social media can report it to the managers for blocked. But on some websites, such things cannot be done, so those who feel victimized ended up doing the same thing to the first attack. Cyberwar through words will continue without end. State responses alone will never be suﬃcient. This happens for several reasons. First, the possibility of anonymity; second, the rapidly growing anarchy in cyberspace as a form of culture wild-wild west; the third, still weak law enforcement in the field of cybercrime – especially religious hate speech; fourth, the possibility of committing crime outside the criminal jurisdiction of a country; and fifth, diminishing of tolerant awareness. There should be a criminal policy and strong in handling this crime, and growing healthy behaviors for Internet users to communicate with other users.Keywords: cybercrime; religious hate speech; internet; anonymity; anarchy.